Using Implicit Economic Multipliers to Guide Local Economic Development: An Agricultural Example in Brevard County, Florida - Rodney L. Clouser; Mohammad Rahmani; Alan Hodges; Jim Fletcher (EDIS)
FE839, an 8-page fact sheet by Rodney L. Clouser, Mohammad Rahmani, Alan Hodges, and Jim Fletcher, provides an example of information for a Florida county, using Brevard County as a model, that can assist in the economic development decision process, which can be completed for minimal expenditures and can aid in the success of economic development efforts. Includes references. Published by the UF Department of Food and Resource Economics, August 2010.